Low Body Mass Index but Not Obesity Is Associated With In-Hospital Adverse Events and Mortality Among Implantable Cardioverter-Defibrillator Recipients: Insights From the National Cardiovascular Data Registry - Hsu, Jonathan C. (Blackwell Publishing Ltd, 2012)
BACKGROUND: Implantable cardioverter-defibrillators (ICDs) are placed in patients at risk for sudden cardiac death, but the procedure may cause adverse events. Patient body habitus may be an important factor responsible for ICD implantation complications. We assessed whether underweight or obese compared with normal weight patients, as defined by body mass index (BMI), were at increased risk for adverse events from ICD implantation. METHODS AND RESULTS: We studied 83 312 first-time ICD recipients in the National Cardiovascular Data Registry-ICD Registry implanted between April 2010 and June 2011. Using hierarchical multivariable logistic regression adjusted for patient demographic and clinical characteristics, we examined the association of BMI with in-hospital complications, length of hospital stay, and mortality. Underweight (BMI ≤18.5 kg/m(2)) patients comprised 1.7% of the cohort (n=1434), whereas obese (BMI≥30 kg/m(2)) patients comprised 40.1% (n=33 339). Overall, a higher proportion of underweight patients experienced complications (normal weight, 2.3%; obese, 2.1%; underweight 5.2%; P<0.0001) and death (normal weight, 0.3%; obese, 0.3%; underweight 0.8%; P=0.026) as a result of ICD implantation. After multivariable adjustment, underweight ICD recipients had a greater odds of complications (odds ratio [OR], 2.15; 95% confidence interval [CI], 1.68 to 2.75; P<0.0001), hospital stay >3 days (OR, 1.62; 95% CI, 1.38 to 1.89; P<0.0001), and in-hospital death (OR, 2.27; 95% CI, 1.21 to 4.27; P=0.011) compared with normal weight patients. Obese patients did not exhibit any meaningful differences in the same outcomes. CONCLUSIONS: In a large, real-world population, underweight first-time ICD recipients experienced significantly more periprocedural complications, prolonged hospital stays, and in-hospital death compared with normal weight patients.